Proposta de uma ferramenta de gestão de indicadores financeiros e não financeiros para empresa do ramo farmaceutico - Silva, Maruza Adriana Mayer da (Universidade do Vale do Rio dos Sinos, 2011)
This work aims to propose a model of Panel of financial and non-financial indicators based on the methodology of strategy management tool Balanced Scorecard (BSC), for a retail company that operates in the pharmaceutical industry within the State of Rio Grande do Sul. For both, the theoretical reference, discussed the main concepts related to BSC, BSC methodology such as, perspectives, strategy map, performance indicators and Executive Dashboard. Search this is a case study, and for collecting data used the feature of semi structured interviews, conducted with the managers and the company's employees, on-site observation and documentary analysis. The analysis of data occurred in steps, first sought to identify the strengths, weaknesses, threats and opportunities. As a result, for the structuring of the Panel, was made the lifting of the goals, indicators and strategies of the four perspectives, and each proposed indicator had its argumentation of the necessity of monitoring and control. Finally, given the goal of the research presented the proposal of the Panel to the managers of the company.
Keywords: Balanced Scorecard; Planejamento estratégico; Indicadores financeiros; Indicadores não financeiros; Painel de controle executivo; Strategic planning; Financial indicators; Non-financial indicators; Executive dashboard